Summary of schemes for the assistance of the unemployable blind (1930)
1930 1930 1930s 6 pages 5. Leeds, cont. a week taken into account. For daughters over 21 years of age earning over 20/- a week taken into account. Lodgers - 4/- in the £1 taken into account. Liverpool. Augmented to 25/- a week. Augmented to 52 2/-. a week - husband & wife, both blind residing in same house. Must be resident in area for at least 12 months. Newcastle Augmented to 25/- a week. Must be resident in area at least 12 months. Income of blind persons concerned only is taken into account. Not eligible Beggars. Northampton. Augmented to 51 a week. Must be resident in area at least 2 years. Council contribute £750 per annum, towards cost which is borne by voluntary association. Norwich. Augmented to 27/6 a week. Must be resident in area at least 12 months. In assessing means the following are taken into account:- (a) Whole means of blind person. (b) Fair proportion of the value of board and lodgings where the person is living with parents or sons or daughters who, it is considered, are able to bear a share of the net cost. (c) One-half of the joint means of husband & wife where one of them is blind. Nottingham. Augmented to 15/- a week. Guardians do not take into account grant to blind persons when calculating relief for dependents. Oxford. Augmented to 51 per week - single persons living alone. Persons who are members of a household are dealt with on their merits. Council contribute at the rate of 54 per head per annum in respect of each blind person on the register. Plymouth. Augmented to £1 a week. Portsmouth. Augmented to £1 a week. Reading. Augmented to 15/- a week, exclusive of rent single persons. Augmented to 15/0 a week, blind persons living with blood relatives where net income of household is less than 15/-a week in respect of adults and 7/6 a week for children to maximum of three. St. Helens. Augmented to £1 a week. 292/841.4/1/40